Exercise Training Improved Longitudinal Intrinsic Left Ventricle Function in Heart Failure with Preserved Ejection Fraction - Santoso, Anwar; Purwowiyoto, Sidhi Laksono; Purwowiyoto, Budhi Setianto; Soesanto, Amiliana Mardiana (International Journal of Angiology, 2019)
Exercise improves morbidity, fatality rate, and quality of life in heart failure with low ejection fraction, but fewer data available in heart failure with preserved ejection fraction (HFPEF).The purpose of this study is to test the hypothesis that exercise training might improve the longitudinal intrinsic left ventricular (LV) function in HFPEF patients.This quasi-experimental study had recruited 30 patients with HFPEF. Exercise training program had been performed for a month with a total of 20 times exercise sessions and evaluated every 2 weeks. Echocardiography was performed before sessions, second week and fourth week of exercise training. Six-minute walk tests (6MWTs) and quality-of-life variables using Minnesota living with HF scoring and the 5-item World Health Organization Well-Being Index scoring were measured before and after exercise as well.Left ventricular filling pressure, represented by the ratio of early diastolic mitral flow velocity/early diastolic annular velocity and left atrial volume index, improved during exercise. The longitudinal intrinsic LV function, represented by four-chamber longitudinal strain, augmented during exercise (p < 0.001). Aerobic capacity, measured by 6MWT, increased significantly (p = 0.001). Quality of life improved significantly during exercise (p < 0.001).Exercise training was suggested to improve the longitudinal intrinsic LV function and quality of life in HFPEF. Clinical Trial Registration: ACTRN12614001042639.
Keywords: heart failure with preserved ejection fraction; 6-minute walk test; four-chamber longitudinal strain; Minnesota living with heart failure